Sex differences in correlates of obesity indices and blood pressure among Malay adults in Selangor, Malaysia - Ahmad Norfazilah; M. S. Juliana; M. N. Azmawati (South African Family Practice)
Background: Obesity is a risk factor for many chronic diseases and related morbidity and mortality. It is imperative to identify the best index of obesity which has the strongest relationship to blood pressure in various populations. The main aim of this study was to determine the sex diﬀerences in correlates of four frequently used obesity indices among Malaysians.